Syllable as a Synchronization Mechanism That Makes Human Speech Possible - Yi Xu (Brain Sciences)
Speech is a highly skilled motor activity that shares a core problem with other motor skills: how to reduce the massive degrees of freedom (DOF) to the extent that the central nervous control and learning of complex motor movements become possible. It is hypothesized in this paper that a key solution to the DOF problem is to eliminate most of the temporal degrees of freedom by synchronizing concurrent movements, and that this is performed in speech through the syllable—a mechanism that synchronizes consonantal, vocalic, and laryngeal gestures. Under this hypothesis, syllable articulation is enabled by three basic mechanisms: target approximation, edge-synchronization, and tactile anchoring. This synchronization theory of the syllable also offers a coherent account of coarticulation, as it explicates how various coarticulation-related phenomena, including coarticulation resistance, locus, locus equation, diphone, etc., are byproducts of syllable formation. It also provides a theoretical basis for understanding how suprasegmental events such as tone, intonation, phonation, etc., are aligned to segmental events in speech. It may also have implications for understanding vocal learning, speech disorders, and motor control in general.